In-vivo oogenesis of oogonial and mesenchymal stem cells seeded in transplanted ovarian extracellular matrix - Leila Mirzaeian; Farideh Eivazkhani; Maryam Saber; Ashraf Moini; Fereshteh Esfandiari; Mojtaba Rezazadeh Valojerdi; Rouhollah Fathi (BMC, 2023)
Abstract Objective (s) One way to overcome the recurrence of cancer cells following ovarian tissue transplantation is to use decellularized tissues as a scaffold that does not have any cellular components. These cell-free scaffolds can be seeded with different type of stem cells for ovarian restoration. Materials and methods OSCs, PMSCs and BMSCs (oogonial, peritoneal and bone marrow mesenchymal stem cells, respectively) were seeded into human decellularized ovarian tissue as 4 groups: Scaffold + OSCs (SO), Scaffold + OSC + PMSCs (SOP), Scaffold + OSC + BMSCs (SOB) and Scaffold + OSC + PMSCs + BMSCs (SOPB). The produced grafts were transplanted into the sub-peritoneal space of ovariectomized NMRI mice as artificial ovary (AO). The expression of Vegf, CD34, Gdf9, Zp3, Ddx4, Amh and Lhr genes in AOs were measured by qRT-PCR. Also, histotechniques were considered to detect the anti GFP, PCNA, VEGF, GDF9, ZP3 and AMH proteins. Results H & E staining showed follicle-like structures in all groups; the number of these structures, in the SOP and SOB groups, were the highest. In SO group, differentiation ability to oocyte and granulosa cells was observed. Endothelial, oocyte, germ, and granulosa cell-like cells were specially seen in SOP and angiogenesis capability was more in SOB group. However, angiogenesis ability and differentiation to theca cell-like cells were more often in SOPB group. While none of the groups showed a significant difference in AMH level, estradiol levels were significantly higher in SOPB group. Conclusion Integration of OSCs + PMSCs and those OSCs + BMSCs were more conducive to oogenesis.